Udział koncepcji psychologicznych w kształtowaniu podstaw teorii i praktyki oddziaływań resocjalizacyjnych - Ambrozik, Wiesław (Wydawnictwo Naukowe UAM, 2013)
This article focuses on showing psychological models that played a special role in the development of the theory and practice of social rehabilitation. Based on these approaches, a number of methods have been developed, including assessment tools and treatment in social rehabilitation of both juvenile and adult offenders.
Psychological Models in the Development of the Theory and Practice of Social Rehabilitation
Keywords: hormic psychology/hormism; psychoanalysis; social rehabilitation assessment; treatment